Ectonucleotidase Inhibitory and Redox Activity of Imidazole‐Based Organic Salts and Ionic Liquids. (23rd October 2018) - Boldescu, Veaceslav; Sucman, Natalia; Hassan, Sidra; Iqbal, Jamshed; Neamtu, Mariana; Lecka, Joanna; Sévigny, Jean; Prodius, Denis; Macaev, Fliur
Abstract: Cytotoxicity against cancer and normal cells, inhibition of ectonucleotidase, and redox properties of a new group of imidazole‐based organic salts and ionic liquids were studied. The tetrachloroferrate salt of a 1‐methylimidazole derivative of salicylic aldehyde had most prominent inhibitory activity against ectonucleotidase as well as a higher cytotoxicity against HeLa cells and lower cytotoxicity against BHK‐21 cells than the reference compound carboplatin. The studied compounds exhibited a moderate level of antioxidant activity with better results for the salicylic aldehyde derivatives than for spiropyrans. Moreover, these compounds did not generate singlet oxygen. Abstract : Salty talk : The reported tetrachloroferrate salt of a 1‐methylimidazole derivative of salicylic aldehyde has higher cytotoxicity against HeLa cells and lower cytotoxicity against BHK‐21 cells than carboplatin. The studied compounds induce stronger inhibition of ectonucleotidase than carboplatin, and their biological effects are one of the main mechanisms of their antiproliferative activity.